Indigenous Cellulosic Raw Materials for the Production of Pulp, Paper and Board - Part VIII.-Writing and Printing Papers From Boswellia serrata , Roxb. (Salai) - Bhat, R. V.; Gura, S. R. D.; Panda, S. P. (Indian Forester, 1952)
Laboratory experiments carried out in this Institute on the production of bleached chemical pulp from Boswellia serrata ( salai ) are described. The results of pilot plant experiments are also included. Two samples of printing paper made from mixtures of Boswellia serrata pulp and bamboo pulp are appended. These experiments have shown that writing and printing papers with suitable strength properties can be prepared from Boswellia serrata using 25-40% of bamboo pulp in the furnish. As the chemical pulp from Bosmellia serrata is short-fibred, it is essential to add bamboo or other long-fibred pulp to the furnish.